Will REDD+ work ?: The need for interdisciplinary research to address key challenges - Visseren-Hamakers, I.J.; Gupta, A.K.; Herold, Martin; Peña-Claros, M; Vijge, M.J. (Elsevier, 2012)
In this article, we draw on the contributions to this issue to address the question 'Will REDD+ work?'. We do so by differentiating between how, where and when REDD+ might work. The article shows how issues of scope, scale and pace of REDD+ are related, and how interdisciplinary research can help to distill the lessons learned from REDD+ efforts currently underway. Important research areas include the drivers of deforestation and forest degradation, monitoring, reporting and verification, co-benefits, governance capacity, linkages with related policies, and the environmental and social impacts of REDD+. In concluding, we highlight the role of interdisciplinary research in supporting the different actors involved in REDD+ to cope with the inherent heterogeneity and complexity of REDD+.